QTL mapping of a novel genomic region associated with high out-crossing rate derived from Oryza longistaminata and development of new CMS lines in rice, O. sativa L. - Prahalada, G.D.; Marathi, Balram; Vinarao, Ricky; Kim, Sung-Ryul; Diocton, Reynaldo; Ramos, Joie; Jena, Kshirod K. (Springer, 2021)
High seed cost due to poor seed yield severely limits the adoption of hybrid rice by farmers. Increasing the out-crossing rate is one of the key strategies to increase hybrid seed production. Out-crossing rate is highly influenced by the size of female floral traits, which capture pollen grains from male donor plants. In the current study, we identified 14 QTLs derived from the perennial wild rice Oryza longistaminata by composite interval mapping for five key floral traits: stigma length (five), style length (three), stigma breadth (two), stigma area (one), and pistil length (three). QTL analysis and correlation studies revealed that these stigma traits were positively correlated and pleiotropic to the stigma length trait. We selected the major-effect QTL qSTGL8.0 conferring long stigma phenotype for further fine mapping and marker-assisted selection. The qSTGL8.0 (~ 3.9 Mb) was fine mapped using newly developed internal markers and was narrowed down to ~ 2.9 Mb size (RM7356–RM256 markers). Further, the flanking markers were validated in a segregating population and in progenies from different genetic backgrounds. The markers PA08-03 and PA08-18 showed the highest co-segregation with the stigma traits. The qSTGL8.0 was introgressed into two cytoplasmic male sterile (CMS) lines, IR58025A and IR68897A, by foreground, background, and trait selection approaches. The qSTGL8.0 introgression lines in CMS backgrounds showed a significantly higher seed setting rate (2.5–3.0-fold) than the original CMS lines in test crosses with their corresponding maintainer lines. The newly identified QTLs especially qSTGL8.0, will be quite useful for increasing out-crossing rate and this will contribute to increase seed production and decrease seed cost.